High‐Yield Separation of Extracellular Vesicles Using Programmable Zwitterionic Coacervates. Issue 1 (11th November 2022) - Paganini, Carolina; Capasso Palmiero, Umberto; Picciotto, Sabrina; Molinelli, Alessandro; Porello, Ilaria; Adamo, Giorgia; Manno, Mauro; Bongiovanni, Antonella; Arosio, Paolo
Abstract: Programmable coacervates based on zwitterionic polymers are designed as dynamic materials for ion exchange bioseparation. These coacervates are proposed as promising materials for the purification of soft nanoparticles such as liposomes and extracellular vesicles (EVs). It is shown that the stimulus‐responsiveness of the coacervates and the recruitment of desired molecules can be independently programmed by polymer design. Moreover, the polymeric coacervates can recruit and release intact liposomes, human EVs, and nanoalgosomes in high yields and separate vesicles from different types of impurities, including proteins and nucleic acids. This approach combines the speed and simplicity of precipitation methods and the programmability of chromatography with the gentleness of aqueous two‐phase separation, thereby guaranteeing product stability. This material represents a promising alternative for providing a low‐shear, gentle, and selective purification method for EVs. Abstract : Positively charged zwitterionic coacervates are designed to purify extracellular vesicles in high yields. This system combines several advantages of different purification methods, including the scalability of precipitation, the gentle phase of aqueous two‐phase systems, and the programmability of chromatography.